Comparison of Central Corneal Thickness Measurement Using Non-Contact and Contact Pachymetry Devices in Normal Eyes - Sidra Malik, Qamar-ul-Islam (Pakistan Journal of Ophthalmology, 2015)
Purpose: To compare central corneal thickness (CCT) in normal population using contact and non-contact pachymetry devices and to assess the intra operator repeatability of measurement with each device. Materials and Methods: This prospective, cross sectional comparative study evaluated 30 healthy subjects fulfilling the inclusion criteria reporting in AFIO Rawalpindi. CCT was measured in both eyes of subjects using noncontact specular microscope, Dual Scheimpflug analyzer and contact ultrasound pachymeter by a single investigator at the same time of the day. Pearson’s correlation coefficient test was performed to ascertain correlation between pachymetry devices. Intra operator repeatability was analysed using within subjects coefficient of variation/repeatability (CoV) and intra class correlation coefficient (ICC). Results: Sixty eyes of 30 male subjects were analysed. Mean age of study population was 31.03 ± 10.30 years. Mean CCT values were 536.48 ± 35.77 µm, 498.62 ± 34.70 µm and 526 ± 37 µm with Dual Scheimpflug Analyzer , Specular microscope and Ultrasonic pachymeter respectively (p < 0.01). There was significant linear co relation between all measurement modalities (r = 0.804 to r = 0.949) (p < 0.01). Intra operator repeatability was excellent for all devices as indicated by low CoV values (< 0.80%) and high ICC values (> 0.90). Conclusion: All three devices showed excellent intra operator repeatability for CCT measurement making them reliable tools for CCT measurement. Key Words: Central Corneal Thickness, Pachymetry, Repeatability, Microscopy.